Lung Manifestations of IgG4-related Disease. A multifaceted disorder. - Ramponi, Sara; Gnetti, Letizia; Marvisi, Maurizio; Bertorelli, Giuseppina; Chetta, Alfredo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Immunoglobulin (Ig) G4-related disease (IgG4-RD) is a recently described systemic inflammatory disease associated with elevated circulating levels of IgG4. IgG4-RD may affect one or more organs and lesions can present synchronously or metachronously in different organs. Pulmonary involvement of IgG4-related disease includes airway, lung parenchyma, pleura and mediastinum. In this article, we report two cases of IgG4-RD to show the multifaceted manifestations of this disease in the lungs.